A new species of the genus Caprella Lamarck, 1801 (Crustacea, Amphipoda, Caprellidae) from Korea - Heo, Jun-Haeng; Shin, So-Yeon; Kim, Young-Hyo (Zootaxa, 2024)
A new species of the genus Caprella, belonging to the family Caprellidae, has been collected from the East Sea of Korea. The new species, Caprella megabranchia sp. nov., is morphologically similar to C. brevirostris Mayer, 1903, in terms of the shape of the propodus of gnathopod 2 and pereopods 5–7, propodi lacking grasping robust seta. However, the new species can be easily distinguished from C. brevirostris by its entirely circular gills and the anterior convexity of peduncular article 3 in antenna 1. The new species is illustrated and compared to related species C. brevirostris and a key to the Caprella species in Korea is also provided.